The Difference of Knowledge and Primary Preventive for Typhoid Fever between Parents in Rural and Urban Areas to Under-Five Years Children - Yushi Rohana (Jurnal Berkala Epidemiologi, 2016)
Under five years child are vulnerable to infectious diseases, one of which is typhoid fever. Typhoid fever is a disease caused by Salmonella Typhii infection. Indonesia is an endemic area for typhoid fever. The purpose of this study is to analyze the differences in knowledge and primary preventive measures by rural and urban parents in the prevention of typhoid fever in infants. This type of research is observational analytic research with a cross-sectional design. The study population was parents of toddlers in rural and urban areas who attended Preschool. Three of the 36 ECEs were used as samples taken by one stage cluster random sampling. The number of samples in rural areas is 51 parents of toddlers and the number of samples in urban areas is 54 parents of toddlers. Data collection was carried out using a questionnaire. Data analysis techniques using the two free sample T-test and the Wilcoxon Mann-Whitney test. The results of this study indicate there are differences in knowledge (p = 0.014) and primary preventive measures (p = 0.00001) between rural and urban parents about typhoid fever in the prevention of typhoid fever in under five years child. The conclusion of this study is that there are differences in the knowledge and actions of rural and urban parents in the prevention of typhoid fever in under five years child, so it is advisable for toddlers parents to pay attention to and improve hygiene and sanitation to avoid typhoid fever and teach their toddlers to always maintain cleanliness.